A novel vacuum/oxygen hot press sintering approach for the fabrication of transparent PLZT (7.4/70/30) ceramics. Issue 7 (1st April 2021) - Cheng, Haijun; He, Xiyun; Zeng, Xia; Ling, Liang; Qiu, Pingsun; Sun, Dazhi
Abstract: Transparent Lanthanum-modified lead zirconate titanate ceramics (PLZT 7.4/70/30) with low content of excess lead oxide (PbO) were successfully prepared by a novel vacuum/oxygen hot press sintering process. The phase structure, microstructure, electrical properties and electro-optic scattering performance of PLZT ceramics as a function of excess PbO in the starting powders have been studied and analyzed. As a result, these ceramics exhibited an ultra-high optical transmittance (>69.4% at 1064 nm; thickness 1 mm) from visible to near-infrared wavelength. Herein, we significantly reduce the use of PbO as an auxiliary agent for sintering. This puts forward a good route to meet the objectives of environmental protection and sustainable development.